Studying COVID-19 Disease Management: A Review Study - Marziye Najafi; Mortez Nazari; Behrooz Pouragha; Ali Jamal Mohammadi; Najmeh Baghian; Ensieh Ashrafi; Roya Rajaee (Shahid Sadoughi University of Medical Sciences, 2021)
Background: This study has been examined in order to examine the studies conducted on disease management in the field of coronavirus caused disease in the type of COVID-19 in the form of area review regarding the development of coronavirus caused disease as a significant challenge in the 21st century and the importance of managing and controlling this disease. Methods: This study was conducted in the form of a field review to identify non-clinical and non-laboratory aspects of coronavirus in both Persian and English and the keywords such as "corona", "coronavirus", COVID-19 " were searched in the databases from "Scopus", "Web of Science", "PubMed", "SID" as well as "Google Scholar" search engines since the beginning of 2020. Results: The contents were searched in the adopted databases, and a total of 1257 studies were discovered, and eventually, 18 main papers were extracted and applied after applying the inclusion and exclusion criteria. As the results obtained by the studies explain, a high percentage of the papers focused on stress management, crisis control, and management, focusing on employees and providing the solutions to decrease stress, including exercise, establishing beneficial relationships with relaxation, and so on. Conclusion: It is better governments provide remote health care services for patients to diagnose and treat this disease due to the speedy spread of coronavirus, lack of definitive treatment, and absence of sufficient quarantine infrastructure for developed patients. Crisis conditions cause all populations engaged in society to share a common purpose and utilize common values in a cooperative movement and progress.